The September 11 Digital Archive. - Brier, Stephen; Brown, Joshua (Radical History Review)
The article discusses the September 11 Digital Archive, a repository for digital material related to the September 11, 2001 terrorist attacks such as e-mails, digital images, and sound recordings. According to the authors, the archive reveals the many ways in which people experienced and understood the attacks. Details related to the creation of the archive, including discussions between the Center for History and New Media (CHNM) at George Mason University, the American Social History Project/Center for Media and Learning (ASHP) at the City University of New York, and the Alfred P. Sloan Foundation, are discussed. Other topics include the research needs of future historians, access to digital media, and the acquisition of the archive by the U.S. Library of Congress (LOC).